Influence of thermal diffusion on thermoelastic coupling and dissipated energy fields evaluated in the heterogeneous case of a woven composite. (15th March 2023) - Navrátil, L.; Carrere, N.; Le Saux, V.; Marco, Y.; Leclercq, S.
Abstract: This article investigates the effects of thermal diffusion on the evaluation of thermoelastic coupling and dissipated energy fields from infrared measurements. The experimental fields are obtained using the heat build-up protocol applied to a 3D layer-to-layer woven composite. A finite element model based on micro-computed tomography results of the tested specimen was generated for the purpose of simulation/experiment comparisons. Two types of finite element simulations are carried out: mechanical and thermal. The analyses of the numerical and experimental results allow to highlight that the heat conduction inside the investigated specimen has a measurable effect on the thermoelastic coupling and dissipated energy fields. The interpretation of the experimental results obtained at the mesoscale level should therefore be accompanied by analyses of numerical simulations that include diffusion effects. On the other hand, macroscale simulation/experiment comparisons showed that, in the investigated configuration, the diffusion has a negligible effect on the global values averaged over the side face of the tested specimen.